Central Nervous System Demyelination Associated With Immune Checkpoint Inhibitors: Review of the Literature - Oliveira, Marcos C. B.; de Brito, Marcelo H.; Simabukuro, Mateus M. (Frontiers in Neurology, 2020)
Immune checkpoint inhibitors (ICI) are a novel class of antineoplastic treatment that enhances immunity against tumors. They are associated with immune adverse events, and several neurological syndromes have been described, including multiple sclerosis and atypical demyelination. We performed a systematic literature review of case reports with neurological immune adverse events that presented with central nervous system demyelination, up to December 2019. We found 23 cases: seven with myelitis, four isolated optic neuritis, one neuromyelitis optica spectrum disorder, five multiple sclerosis, and six with atypical demyelination. Ipilimumab was the most frequently used ICI (11/23). The median time to develop symptoms from the onset of ICI was 6.5 weeks [range 1.0–43.0], and from last ICI dose was 14 days [range 0–161]. Anatomopathological examination was performed in four cases, with the finding of a T-cell mediated immune response. Outcomes were generally favorable after immunosuppression: 18 patients had improvement or a full recovery, three patients did not respond to treatment, three patients died, and in one, treatment was not reported. We describe the patients' clinical presentation, treatment administered, and outcomes. We further speculate on possible pathophysiological mechanisms and discuss potential treatments that may be worth investigating.